Risk analysis of coal seam floor water inrush based on GIS and combined weight TOPSIS method - Yue Li; Yunpeng Zhang; Yajie Ma; Fangang Meng; Shida Guo (All Earth)
In view of the problem of floor water inrush in the process of deep coal seam mining, propose to establish a risk assessment model for coal seam floor water inrush using GIS and combined weight TOPSIS method. Take coal 12-1 of level −950 in Donghuantuo Coal Mine as an example, the coal seam hosting thickness, coal seam burial depth, fault intensity index, aquifer thickness, water-rich aquifer thickness, first aquiclude thickness and second aquiclude thickness are taken as decisive indexes. Based on actual engineering exploration, the entropy weighted AHP weighted TOPSIS method is used to determine the partition threshold and classification level, analyse the risk of water inrush from coal seam floor, and visualise it based on GIS platform. The results show that the combined weight values of coal seam burial depth and fault scale index are 0.4008 and 0.2201, which have a significant impact on water inrush from the coal seam floor. The zoning threshold for the risk coefficient of water inrush from the 12–1 coal seam floor is 0.478, The overall water inrush risk of the mine field is less. Only a few areas in the southwest of the mine field are water inrush risk areas.